The clinical assessment of studies on orphan drugs in relation to the EMA’s authorization marketing decisions in Europe - Jakubowski, Szczepan; Malinowski, Krzysztof Piotr; Kawalec, Paweł (Frontiers in Pharmacology, 2025)
IntroductionThe main objective of this study was to assess the correlation between the methodological characteristics of clinical trials on orphan drugs and the special statuses granted by the European Medicines Agency (EMA).Material and methodsData were collected for all medicines with orphan designation assigned by 2020. From August 2019 to June 2020, special statuses (authorization statuses and registration requirements) and general information on orphan drugs were obtained from the EMA’s web-based registry. The following clinical data were collected: number of patients, clinical phase, randomization, masking, control group, treatment durations, and safety and efficacy follow-ups. Descriptive, comparative, multivariate, and univariate analyses of data were conducted.ResultsResults were provided for 105 medicines with orphan designation. The odds of an orphan drug receiving conditional approval were lower for studies with randomization (p = 0.002) and active controlled trials (p = 0.010), but they increased in those with a treatment duration of 3–12 months (p = 0.002) and those with a safety and efficacy follow-up of 2–6 months (p = 0.008 and p = 0.035, respectively). Approval under exceptional circumstances was less likely for each additional 1,000 patients included in reference (p = 0.002), randomization (p = 0.024), double blinding (p = 0.033), and active-controlled trials (p = 0.006). However, it was more likely for phase II/III trials (p = 0.039), those with a treatment duration of 3–12 months (p = 0.03), and those with a safety and efficacy follow-up longer than 6 months (p = 0.022 and p = 0.047, respectively).ConclusionThe types of clinical trials and their methodological characteristics are correlated with the EMA’s decisions. Randomization, double blinding, and active-controlled trials reduce the odds of ODs receiving EMA special statuses. In contrast, phase II/III trials, specific durations of treatment, and specific safety and efficacy follow-ups increased these odds.